EFL Teachers’ Roles in Technology-Integrated Instruction Practices at Junior High School - Nabilah, Nada; Siregar, Aisyah; Jayanti, Suci Etri (STIE Bina Karya, 2024)
These days, technology-based learning is essential since it provides media and tools for the process of teaching and learning. However, in addition to all of the effort that teachers put into integrating technology into the classroom, other factors must be taken into consideration, one of which is the teacher's role. The purpose of this study was to find out the efficacy of the roles and digital learning resources that English teachers employ in their classes. The responders to this study were 5 English teachers from various junior high schools in Tebing Tinggi, North Sumatera, in the academic year 2022/2023. In addition, 9 students from each class also involved as the respondents. So the total number of students that participated in this study was 45. A qualitative approach was taken in conducting this study. The researcher used interviews and observation as instruments to get the data required for this study. The results of this study showed that teachers additionally played the roles that were necessary for technology-based learning, including as the operators, mentors for technology use, organizers of technology-based learning, and monitors of digital learning.